ANALYSIS AND MITIGATION OF HAND ARM POWER TOOLS VIBRATION - S. Chiad, Jumaa; A. Bedaiwi, Bashar; Yousif Idrees, Mohannad (Journal of Engineering and Sustainable Development, 2016)
The hard workers are usually suffering from big medical problems after working with vibrating equipment such as compressors and different types of drills. These and many relative problems give a big motivation to study, measure, and analyze the vibration. The data were resulting from the vibration of the power tools to the human hand of the user that is in touch with this vibrating equipment is considered one of the most interesting Biomechanical Engineering. This work studies the vibration frequency, displacement, and velocity acceleration that will be measured at different hand points. The examination was conducted on two workers (subjects) who are different in age, weight, and height. This investigation requires the design and manufacture of vibration measurement systems according to international standards ( ISO 28927-10).ANSYS 15 program was chosen in order to evaluate the numerical results and then compare them with experimental results. Different types were used of Anti-vibration gloves in order to reduce the vibration connecting to the hand-arm workers. The results show that values of acceleration and frequency are increased with the decreasing distance of the sensor point from the drill handle. When using the subject (1) as a grand foundation, the reduction in frequency and acceleration when wearing gloves, The reduction percentage in the metacarpal for the sponge handle is (34.4 %) while in the working gloves is (30.6 %), silicon gloves are (28.6 %), cloth gloves are (26.6 %), and leather gloves are (25.9 %)...